Vegetative propagation of Cecropia obtusifolia (Cecropiaceae) - LaPierre, Louis M (Universidad de Costa Rica, 2001)
Cecropia is a relatively well-known and well-studied genus in the Neotropics. Methods for the successful propagation of C. obtusifolia Bertoloni, 1840 from cuttings and air layering are described, and the results of an experiment to test the effect of two auxins, naphthalene acetic acid (NAA) and indole butyric acid (IBA), on adventitious root production in cuttings are presented. In general, C. obtusifolia cuttings respond well to adventitious root production (58.3 % of cuttings survived to root), but air layering was the better method (93 % of cuttings survived to root). The concentration of auxins used resulted in an overall significantly lower quality of roots produced compared with cuttings without auxin treatment. Future experiments using Cecropia could benefit from the use of isogenic plants produced by vegetative propagation.